Predators modify the temperature dependence of life‐history trade‐offs. Issue 17 (7th August 2018) - Luhring, Thomas M.; Vavra, Janna M.; Cressler, Clayton E.; DeLong, John P.
Abstract: Although life histories are shaped by temperature and predation, their joint influence on the interdependence of life‐history traits is poorly understood. Shifts in one life‐history trait often necessitate shifts in another—structured in some cases by trade‐offs—leading to differing life‐history strategies among environments. The offspring size–number trade‐off connects three traits whereby a constant reproductive allocation ( R ) constrains how the number ( O ) and size ( S ) of offspring change. Increasing temperature and size‐independent predation decrease size at and time to reproduction which can lower R through reduced time for resource accrual or size‐constrained fecundity. We investigated how O, S, and R in a clonal population of Daphnia magna change across their first three clutches with temperature and size‐independent predation risk. Early in ontogeny, increased temperature moved O and S along a trade‐off curve (constant R ) toward fewer larger offspring. Later in ontogeny, increased temperature reduced R in the no‐predator treatment through disproportionate decreases in O relative to S . In the predation treatment, R likewise decreased at warmer temperatures but to a lesser degree and more readily traded off S for O whereby the third clutch showed a constant allocation strategy of O versus S with decreasing R . Ontogenetic shifts in S and O rotated in a counterclockwise fashion as temperature increased and more drastically under risk of predation. These results show that predation risk can alter the temperature dependence of traits and their interactions through trade‐offs. Abstract : Temperature and predation risk have interactive effects on the offspring size–number trade‐off through its underlying constraint (reproductive investment). Thus understanding life‐history responses to environmental change in natural systems requires integrated approaches that incorporate multiple linked traits and the constraints that tether them to one another.